Clinical Observation Current Varicella Encephalitis in Children - O. G. Kimirilova; G. A. Harchenko; A. A. Kimirilov (Детские инфекции (Москва), 2015)
The article presents the clinical picture, the course and outcome of encephalitis caused by the varicella-zoster virus. It is shown that the inclusion in the complex therapy of abnormal nucleoside (Acyclovir and its derivatives), intravenous immunoglobulin, promotes the release of patients from critical conditions to reverse the development of the pathological process.